2006
DOI: 10.1519/18285.1
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of a Caffeine-Containing Supplement on Strength, Muscular Endurance, and Anaerobic Capabilities

Abstract: The purpose of this study was to examine the acute effects of a caffeine-containing supplement on upper- and lower-body strength and muscular endurance as well as anaerobic capabilities. Thirty-seven resistance-trained men (mean +/- SD, age: 21 +/- 2 years) volunteered to participate in this study. On the first laboratory visit, the subjects performed 2 Wingate Anaerobic Tests (WAnTs) to determine peak power (PP) and mean power (MP), as well as tests for 1 repetition maximum (1RM), dynamic constant external re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
88
2
11

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 14 publications
16
88
2
11
Order By: Relevance
“…Caffeine increase intracellular cyclic adenosine monophosphate (c-AMP) by phosphodiesterase inhibition (Tarnopolsky, 2010). Increase in c-AMP would lead to a greater lipolysis, and relationship with regulation of adipose tissue (Davis, Grenn, 2009).Our findings are in line with a number of studies showing no improvement in muscular endurance and muscular strength following caffeine intake (Astorino, Rohmann, Firth, 2008;Beck et al, 2006;Hendrix et al, 2010). Beck et al (2006) showed that supplements containing caffeine do not affect muscular endurance (bench press, leg extension) and leg extension 1RM (muscular strength).…”
supporting
confidence: 83%
See 4 more Smart Citations
“…Caffeine increase intracellular cyclic adenosine monophosphate (c-AMP) by phosphodiesterase inhibition (Tarnopolsky, 2010). Increase in c-AMP would lead to a greater lipolysis, and relationship with regulation of adipose tissue (Davis, Grenn, 2009).Our findings are in line with a number of studies showing no improvement in muscular endurance and muscular strength following caffeine intake (Astorino, Rohmann, Firth, 2008;Beck et al, 2006;Hendrix et al, 2010). Beck et al (2006) showed that supplements containing caffeine do not affect muscular endurance (bench press, leg extension) and leg extension 1RM (muscular strength).…”
supporting
confidence: 83%
“…Beck et al (2006) indicated that consumption of caffeine had no effect on mean power, compared to the placebo.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations